Insight into Binding and Interaction of Docking, Dynamics and Network Pharmacology to Explore the Target on Cancer Inhibitors - Gayathiri, Ekambaram; Prakash, Palanisamy; Pratheep, Thangaraj; Chaudhari, Somdatta Y.; Priyadharshini, Subramanian Deepika; Mani, Thenmozhi; Mahalakshmi, Periysamy (Journal of pharmaceutical innovation, 2024)
Purpose The bioefficacy of accessible chemical structures has been established, leading to some optimization to address these constraints. Methods This study aimed to identify the computational interactions of molecular docking, molecular simulations, and Network Pharmacology, which were used to predict the anticancer efficacy of Capsaicin and Quinidine complexes. Results The molecular docking studies exhibited that the identified phytocompounds had excellent binding energy against all of these target receptors, with 6OP9 affinity binding energy at -8.62 kcal/mol and for 3VHE at -8.18 kcal/mol. Molecular dynamics simulation for 100 ns of MD studies with RMSD and RMSF plots indicated that the ligand is stable, as it establishes interactions within active site residues such as LYS868, ASP1046, PHE1447, LEU14035, and LEU1099, followed by hydrogen bond interactions with THR768, ASP833, PHE834, LEU726, SER728, VAL734, and MET801. Based on human intestinal absorption, bioavailability score, P-glycoprotein, and BBB penetrant data, these are positive physiochemical inhibitors of Capsaicin and Quinidine. In network pharmacology, the essential genes identified were associated with cancer development (HER-2, HER-3), not specific to those that play a role in the carcinogenesis of the breast as well discussed by the targeted therapy trials mentioned above, that is, VEGFR1-3 and FGFR2 versus identification of progression-related genes involved, including ESR1, SRC, and HSP. Conclusions In vivo studies are needed to confirm the anticancer action of cancer regulatory proteins, and clinical trials are required to prove its safety and efficacy in other human subjects.